Effectiveness of sex pheromone traps in the integrated management of Planococcus ficus Signoret (Hemiptera: Pseudococcidae) in vineyards - Narrea-Cango, Mónica; Gómez, Luz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Planococcus ficus (Signoret) represents an economically significant pest in viticulture, requiring timely, innovative, and effective control measures. While the application of sex pheromones in vineyards has primarily focused on mating disruption, there is a lack of studies evaluating their use in mass trapping as a management tool for this pest. This study was conducted in a commercial vineyard of the Crimson Seedless variety in Ica, Peru, and the objective was the efficacy of pheromone-baited traps (CINNAFIC®) deployed from postharvest 2020 through postharvest 2021. During this period, a trap density of 15 traps.ha⁻¹ was maintained, resulting in the capture of 16,927 males, with a peak capture rate of 112.20 males.trap⁻¹.week⁻¹ observed during the berry development stage. The greatest control was observed at harvest, with a 59.12 % reduction in the total mealybug population, highlighted by the production of infestation-free, fully exportable grape clusters, compared to 7 % infestation in control plots. Trap deployment limited mating opportunities, significantly altering the population structure by reducing nymphs and ovipositing females in treated plots. These results demonstrate that integrating pheromone traps with cultural practices and timely applications of pesticides and botanical extracts enables effective mealybug control without exclusive reliance on chemical insecticides. It is concluded that pheromone traps constitute a sustainable, effective, and viable tool for the integrated management of P. ficus in vineyards.